Evalution of the Biological Activity of Pistacia Lentiscus Gum (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Pistacia lentiscus gum is considered as a medicinal value which is characterized by the presence of many active substances included: phenols, flavonoids, hydrolyzed and condensed tannins, saponins, glycosides and anthracenes, in addition to volatile oils, it is anti-microbial and anti-cancer cells. The results of the study confirmed that the efficiency of extracting the active substances is due to the type of solvent used in the extraction, as the results, ethyl acetate considered as the best solvents used to extract the active substances from gum compared to ethyl alcohol and chloroform. The study also showed the inhibitory activity of gum extracts against the tested bacteria and fungi. The cytotoxicity of the extract gum was studied in the meristematic cells of the roots of the onion plant, using concentrations of 0.1% and 0.05%. The studied cytological parameters included chromosomal abnormalities at indirect mitosis. It was found that the effect of the gum extract was clear on the dividing cells in the onion roots at the higher concentration 0.1%, the greater the cytotoxic effect. the concentration of 0.1% of the gum extract prevailed over the cells in the slurry conditions, while the concentration of 0.05% of the gum extract had the lowest effect, and the most frequent chromosomal abnormalities were viscosity. The results of the GTS study confirmed that the gum extract is genetically toxic at the concentrations used in this study.
Keywords: Biological activity; Pistacia lentiscus gum; Anti-microbial; Cytological parameters